Using Grafts and Granulation to Improve Nasal Repair - Gruber, Paul J.; Walen, Scott; Massa, Sean T.; Maher, Ian A. (Facial Plastic Surgery, 2017)
Skin grafts offer a dynamic repair option for nasal defects of appropriate size, depth, and location. Granulation and grafting can successfully be used as stand-alone reconstructive options or in conjunction with flap repair. This article reviews suitable indications for graft and granulation use in nasal repair to achieve optimum functional and esthetic outcomes.
Keywords: nasal; reconstruction; granulation; graft; flap